African (situated) psychologies of boys, men and masculinities - Ratele, Kopano (PINS-Psychology in Society, 2017)
How might psychology less alienatingly study African men and boys? What potential contribution, in other words, might a situated psychology make towards understanding men and boys? Urged by these questions, and grounded in the view that there is still relatively little concerning Africa for itself, as well as much that is dehumanising of Africans within (North American and western European-centred) psychology this article seeks to present what I refer to as (African) situated psychologies, and more specifically (African) situated psychologies of boys, men and masculinities. Whilst the article is generally meant to contribute to the development of African psychology, because of an abiding interest in boys, men and masculinities, the article is also specifically intended to show how we might go about centring Africa in psychological studies of boys, men and masculinities. The basic argument is that attachment to (North American- or Western European-centred) psychology and Africa is inherently estranging, and what may be necessary is to critically trouble globally hegemonic traditions into which psychology students, teachers, therapists, and researchers located in Africa and with an interest in boys and men are hailed. Four different orientations in studies of psychology of masculinities are outlined, namely, a psychology of African boys, men and masculinities; psychological African studies of boys, men and masculinities; a more cultural African psychology of boys, men ad masculinities; and a more critical African psychology of boys, men and masculinities.